Fundamentals of continuum mechanics : with applications to mechanical, thermomechanical, and smart materials - Bechtel, Stephen E. (Stephen Eric); Lowe, Robert L.; ScienceDirect eBooks (Amsterdam ; Boston : Academic Press, an imprint of Elsevier, 2014)
"Fundamentals of Continuum Mechanics provides a clear and rigorous presentation of continuum mechanics for engineers, physicists, applied mathematicians, and materials scientists. This book emphasizes the role of thermodynamics in constitutive modeling, with detailed application to nonlinear elastic solids, viscous fluids, and modern smart materials. While emphasizing advanced material modeling, special attention is also devoted to developing novel theories for incompressible and thermally expanding materials. A wealth of carefully chosen examples and exercises illuminate the subject matter and facilitate self-study"--Page 4 of cover.
"Transferred to digital printing in 2014"--Title page verso.
Includes bibliographical references (pages 321-324) and index.
Print version record.
Elsevier
Keywords: Continuum mechanics; Continuum mechanics; Electronic books